The Measurement of Islamic Unit Trust Investment Decision in Malaysia: An Exploratory Factor Analysis - Yusuff, Noraini; Mansor, Fadillah; Hamed, Abu Bakar (UUM Press, 2017)
The objective of this study is to develop the constructs in Islamic Unit Trust Investment Decision (IUTID) and examine its determinants. The determinants of Islamic Unit Trust Investment Decision are Islamic Financial Literacy (IFL), Information Sources (IS), Investment Risk (IR), Religiosity (RE) and Product Knowledge (PK). The measurement developed is based on the literature review and has been validated by the construct's experts, and among Islamic Unit Trust Investors. The validity and reliability test have tested to all the constructs. The data have been analyzing using SPSS. Results of the analysis show that Islamic unit trust investment decision can be measured using ten (10) items of investment selection criteria. The others determinants such as Islamic financial literacy construct consists of seven (7) items, information sources construct consists of ten (10) items, investment risk consists of eight (8) items, religiosity consists of eight (8) items and product knowledge consists of seven (7) items. The variance of the construct shows that information sources have the highest variance followed by investment risk, Islamic financial literacy, religiosity and product knowledge. These instruments can be used by unit trust companies, the authorities of Islamic unit trust (FIMM, SC, BNM) and other banking's product to understand the behavior of their clients and later, can implement it to the expected new customers.